Effect of Wilting on Carbohydrates during Incubation of Excised Bean Leaves in the Dark - Stewart, Cecil R. (1971)
Excised bean (Phaseolus vulgaris) leaves were used to compare the changes in various carbohydrates during dark incubation in a wilted and turgid condition. After a rapid (less than 1 hour) wilt, leaves were incubated at a constant water content (75% of original fresh weight). The starch content of the wilted leaves decreased faster than it did in the turgid leaves. This accelerated starch loss was accompanied by an increase in free (alcohol-soluble) sugars, while no similar increase was observed in the turgid leaves. The increase in free sugars in the wilted leaves during accelerated starch loss was sufficient to account for the decreased starch content in wilted leaves compared to turgid leaves. Thus, total carbohydrate decreased at the same rate in both wilted and turgid leaves during dark incubation. The free sugar which accumulated in the wilted leaves was mainly sucrose. There was no increase in sucrose content of turgid leaves during incubation, although there was a rapid loss of starch. Glucose and fructose also increased during incubation, but there was no difference between the wilted and turgid leaves. These results suggest that wilting of detached leaves caused a conversion of starch to sucrose in the dark.